391 History of the Canadian Pet Food Industry- A Veterinarians' Point of View. (7th December 2018) - MacKay, C
Abstract: Living in the veterinary world of pets from 1957 to today, I experienced the major changes in the Canadian/Global pet food industry. During the early days, I was vaguely aware of the ongoing change to pet foods, from a largely canned/meat-based product to semi-moist and then to dry formulations. Once inside the pet food industry, as the Director of Professional Affairs for Hill's Pet Nutrition Canada, I began to see and understand how and why many of the changes happened. In the early days, after the development of the internal combustion engine, the primary source of protein came from horse meat. Horses had gone from the source of all work, transportation and pleasure use to, in many cases, an unwanted mouth to feed that required care for in both agriculture and cities of the time. Following that this talk will take us through the interesting challenges of consolidation, industrialization and regulation of the pet food industry in Canada, including the size and complexity of the Canadian industry to the global market. Most nutritionists and veterinarians are interested in the actual nutrients to provide an adequate or superior diet. Unfortunately, it appears that the marketing of cat and dog food products appear, in many cases, to be based on nutritional myths and partial truths that mirror similar approaches in products sold for human use.